Identification of candidate genes involved in isoquinoline alkaloids biosynthesis in Dactylicapnos scandens by transcriptome analysis - Si Mei He (Nature Portfolio, 2017)
Abstract Dactylicapnos scandens (D. Don) Hutch (Papaveraceae) is a well-known traditional Chinese herb used for treatment of hypertension, inflammation, bleeding and pain for centuries. Although the major bioactive components in this herb are considered as isoquinoline alkaloids (IQAs), little is known about molecular basis of their biosynthesis. Here, we carried out transcriptomic analysis of roots, leaves and stems of D. scandens, and obtained a total of 96,741 unigenes. Based on gene expression and phylogenetic relationship, we proposed the biosynthetic pathways of isocorydine, corydine, glaucine and sinomenine, and identified 67 unigenes encoding enzymes potentially involved in biosynthesis of IQAs in D. scandens. High performance liquid chromatography analysis demonstrated that while isocorydine is the most abundant IQA in D. scandens, the last O-methylation biosynthesis step remains unclear. Further enzyme activity assay, for the first time, characterized a gene encoding O- methyltransferase (DsOMT), which catalyzes O-methylation at C7 of (S)-corytuberine to form isocorydine. We also identified candidate transcription factor genes belonging to WRKY and bHLH families that may be involved in the regulation of IQAs biosynthesis. Taken together, we first provided valuable genetic information for D. scandens, shedding light on candidate genes involved in IQA biosynthesis, which will be critical for further gene functional characterization.